Existing data analysis in pediatric critical care research - Bennett, Tellen D.; Spaeder, Michael C.; Matos, Renee I.; Watson, R S.; Typpo, Katri V.; Khemani, Robinder G.; Crow, Sheri; Benneyworth, Brian D.; Thiagarajan, Ravi R.; Dean, J M.; Markovitz, Barry P. (Frontiers in Pediatrics, 2014)
Our objectives were to review and categorize the existing data sources that are important to pediatric critical care medicine (PCCM) investigators and the types of questions that have been or could be studied with each data source. We conducted a narrative review of the medical literature, categorized the data sources available to PCCM investigators, and created an online data source registry. We found that many data sources are available for research in PCCM. To date, PCCM investigators have most often relied on pediatric critical care registries and treatment- or disease-specific registries. The available data sources vary widely in the level of clinical detail and the types of questions they can reliably answer. Linkage of data sources can expand the types of questions that a data source can be used to study. Careful matching of the scientific question to the best available data source or linked data sources is necessary. In addition, rigorous application of the best available analysis techniques and reporting consistent with observational research standards will maximize the quality of research using existing data in PCCM.